Filter penetration and breathing resistance evaluation of respirators and dust masks. Issue 2 (1st February 2017) - Ramirez, Joel; O'Shaughnessy, Patrick
ABSTRACT: The primary objective of this study was to compare the filter performance of a representative selection of uncertified dust masks relative to the filter performance of a set of NIOSH-approved N95 filtering face-piece respirators (FFRs). Five different models of commercially available dust masks were selected for this study. Filter penetration of new dust masks was evaluated against a sodium chloride aerosol. Breathing resistance (BR) of new dust masks and FFRs was then measured for 120 min while challenging the dust masks and FFRs with Arizona road dust (ARD) at 25°C and 30% relative humidity. Results demonstrated that a wide range of maximum filter penetration was observed among the dust masks tested in this study (3–75% at the most penetrating particle size (p < 0.001). The breathing resistances of the unused FFRs and dust masks did not vary greatly (8–13 mm H2 O) but were significantly different (p < 0.001). After dust loading there was a significant difference between the BR caused by the ARD dust layer on each FFR and dust mask. Microscopic analysis of the external layer of each dust mask and FFR suggests that different collection media in the external layer influences the development of the dust layer and therefore affects the increase in BR differently between the tested models. Two of the dust masks had penetration values < 5% and quality factors (0.26 and 0.33) comparable to those obtained for the two FFRs (0.23 and 0.31). However, the remaining three dust masks, those with penetration > 15%, had quality factors ranging between 0.04–0.15 primarily because their initial BR remained relatively high. These results indicate that some dust masks analysed during this research did not have an expected very low BR to compensate for their high penetration.